PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENUNGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 143 PEKANBARU - Qolby Noor Fasya; Hendri Marhadi; Munjiatun Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTBackground of the problem in this study is the low learning outcomes IPS Elementary School fourth grade students 143 Pekanbaru , the average grade 68.57, while the value KKM IPS is 70. This study aims to improve learning outcomes IPS Elementary School fourth grade students 143 Pekanbaru applying cooperative learning model Numbered Heads Together ( NHT ) . The research was conducted on November 13, 2013 to December 4, 2013 that carried as much as 3 cycles . This thesis presents the results obtained from the study before action replay value with an average of 68.57 , an increase in the first cycle with an average of 69.71 . In the second cycle increased by an average of 76.57 , and an increase in cycle III with an average of 87.15 . Teacher activity the first cycle and the first meeting of 66.67 % the second meeting increased to 75 % . The first meeting of the second cycle of 83.33 % and the second meeting increased to 87.50 % . The third cycle of the first meeting and the second meeting 91.67 % increase to 95.83 % . Student activity the first cycle the first meeting with an average of 50 % and a second meeting increased to 62.50 % . At the first meeting of the second cycle with an average of 75 % and at the second meeting increased to 87.50 % . At the first meeting of the third cycle with an average of 91.67 % and a second meeting increased to 95.83 % . From the results of studies in fourth grade Elementary School 143 Pekanbaru prove that the application of cooperative learning model Numbered to improve learning outcomes IPS Elementary School fourth grade students 143 Pekanbaru . Keywords : Cooperative Learning Model tipe Numbered Heads Together (NHT), IPS Learning Outcomes .